Cuisine as a Symbolic Asset of a Destination: The Construction of Consumer Experience and Brand Identity as Tourist Attractions - Dangi Dangi; Vanessa Gafar; Agus Rahayu; Alfira Sofia (Lembaga Bale Literasi, 2026)
This study aims to determine the relationship between the culinary experience of Empal Gentong as a symbolic asset and the construction of regional identity branding on tourist attraction. This quantitative study took a sample of 337 respondents selected using random sampling and analyzed using Partial Least Square Structure Equation Modeling (PLS SEM). The results show a significant relationship between the Empal Gentong culinary experience as a symbolic asset of the destination and the construction of branding identity and regional branding identity. The Empal Gentong culinary experience does not have a significant effect on tourist attraction. Meanwhile, the construction of branding identity and regional branding identity plays a significant role in mediating the influence of the Empal Gentong culinary experience on tourist attraction. The results of this study are expected to contribute to scientific knowledge and provide evaluation and improvement materials for culinary practitioners, tourism activists, the community, and the Cirebon Regency Government in formulating tourism development strategies to strengthen tourist attraction.